Analisis Snyder Dalam Keputusan Abstain Indonesia Dalam Sidang Majelis Umum PBB Tahun 2013 Mengenai Perjanjian Perdagangan Senjata: Snyder’s Analysis on Indonesia’s Abstention Stance in the 2013 UN General Assembly Session on Arms Trade Treaty - Monica Rhasintya (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2020)
Illegal circulation of Small Arms and Light Weapons (SAWL) motivates countries to discuss the legal bindings needed to be devised to overcome them. The formulation of controlling SAWL consisted of various stages and processes which eventually formed the Arms Trade Agreement and were tried at the UN General Assembly session in 2013. Indonesia, which initially supported the existence of legal instruments to oversee the movement of the SAWL, decided to abstain. Using the literature study method, this research intends to explain the reasons for Indonesia's abstention and to analyze the decision-making process using Snyder's perspective. Keywords: decision making, national interests, arms trade treaty, small arms, Indonesia